2001
DOI: 10.1007/s003300000583
|View full text |Cite
|
Sign up to set email alerts
|

CT appearance of solitary and multiple cystic and cavitary lung lesions

Abstract: Cystic and cavitary lung lesions constitute a spectrum of pulmonary diseases diagnosed in both children and adults. We reviewed the CT findings of the most common cystic and cavitary lung lesions and we defined useful morphological criteria that will help radiologists to distinguish benign from malignant cavitary lesions. However, in many cases the considerable overlap in morphological features of benign and malignant cavities renders transthoracic needle biopsy necessary to establish the correct diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
0
41
0
1
Order By: Relevance
“…However, previous studies have shown that they are more commonly associated with primary squamous cell carcinoma. Cavitating lung metastases have been reported with primary lung, head and neck, thyroid, breast, bone, kidney, pancreas, colon and rectum, urinary bladder, penis, testis (Figure 26), uterine, cervix and skin carcinomas (4,24). The aetiology of the formation of a cavity is not clear.…”
Section: Metastatic Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…However, previous studies have shown that they are more commonly associated with primary squamous cell carcinoma. Cavitating lung metastases have been reported with primary lung, head and neck, thyroid, breast, bone, kidney, pancreas, colon and rectum, urinary bladder, penis, testis (Figure 26), uterine, cervix and skin carcinomas (4,24). The aetiology of the formation of a cavity is not clear.…”
Section: Metastatic Diseasementioning
confidence: 99%
“…In the liteature, several forms of pulmonary aspergillosis have been described, including saprophytic (aspergilloma), invasive, semi-invasive and allergic bronchopulmonary aspergillosis (ABPA) (4,20). The radiographic presentations of pulmonary aspergillosis vary depending on the form of the disease and the patient's clinical setting.…”
Section: Fungal Infectionsmentioning
confidence: 99%
See 3 more Smart Citations